Setting a Course for Preventing Hepatitis E in Low and Lower-Middle-Income Countries: A Systematic Review of Burden and Risk Factors. (13th April 2021) - Koyuncu, Aybüke; Mapemba, Daniel; Ciglenecki, Iza; Gurley, Emily S; Azman, Andrew S
Abstract: Background: Hepatitis E virus (HEV) is responsible for outbreaks of acute jaundice in Africa and Asia, many of which occur among displaced people or in crisis settings. Although an efficacious vaccine for HEV has been developed, we lack key epidemiologic data needed to understand how best to use the vaccine for hepatitis E control in endemic countries. Methods: We conducted a systematic review of articles published on hepatitis E in low-income and lower-middle-income countries in Africa and Asia. We searched PubMed, Scopus, and Embase databases to identify articles with data on anti-HEV immunoglobulin (Ig)G seroprevalence, outbreaks of HEV, or risk factors for HEV infection, disease, or death, and all relevant data were extracted. Using these data we describe the evidence around temporal and geographical distribution of HEV transmission and burden. We estimated pooled age-specific seroprevalence and assessed the consistency in risk factor estimates. Results: We extracted data from 148 studies. Studies assessing anti-HEV IgG antibodies used 18 different commercial assays. Most cases of hepatitis E during outbreaks were not confirmed. Risk factor data suggested an increased likelihood of current or recent HEV infection and disease associated with fecal-oral transmission of HEV, as well as exposures to blood and animals. Conclusions: Heterogeneity in diagnostic assays used and exposure and outcome assessment methods hinder public health efforts to quantify burden of disease and evaluate interventions over time and space. Prevention tools such as vaccines are available, but they require a unified global strategy for hepatitis E control to justify widespread use. Abstract : Existing epidemiologic data are insufficient to identify temporal or geographic trends in HEV risk. Unified guidance for measuring hepatitis E disease burden and risk factors is urgently needed to generate evidence to justify widespread use of the existing vaccine.